Additive for lithium ion secondary battery positive electrode material, and lithium ion secondary battery positive electrode material and lithium ion secondary battery comprising the same
Patent Information
- Application Number
- CN202580023949.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-02
- Filing Date
- 2025-03-24
- Publication Date
- 2026-10-30
AI Technical Summary
锰会从作为正极活性物质的锰酸锂中溶出,并由于正极活性物质的变化、溶出的锰在负极表面及隔膜上的析出、电解液的劣化等各种作用,导致电池的循环特性劣化、保存容量降低
[0027]在锂离子二次电池中,与未在正极材料中添加本发明的正极材料用添加剂的情况相比,在正极材料中添加本发明的正极材料用添加剂时,能够提高锂离子二次电池的性能。
Smart Images

Figure CN123023149A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to additives for positive electrode materials used in lithium-ion secondary batteries, as well as positive electrode materials for lithium-ion secondary batteries and lithium-ion secondary batteries containing the additives. Background Technology
[0002] In recent years, the miniaturization and lightweighting of mobile information terminals such as mobile phones, laptops, and smartphones have developed rapidly. As their driving power source, lithium-ion secondary batteries, which are small and high-capacity sealed batteries, have been widely used.
[0003] Typically, lithium-ion secondary batteries use a negative electrode and a positive electrode. The negative electrode uses carbonaceous materials that can be doped or dedoped with lithium as the active material, and the positive electrode uses a composite oxide of lithium and transition metal oxides as the active material. The manufacturing method is as follows: the negative electrode and the positive electrode are coated on strip-shaped negative electrode current collectors and positive electrode current collectors respectively, and then stacked in layers with a separator and covered with an outer packaging material; or, these components are stacked and wound into a spiral shape, and the resulting wound body is housed in a battery can.
[0004] To improve ease of use, there is a demand for further performance enhancements in lithium-ion rechargeable batteries. Typically, this includes requirements for faster charging, increased discharge current, and extended lifespan (maintaining high battery capacity even after repeated charge-discharge cycles). Various research and development efforts have been undertaken to address these needs.
[0005] Patent Document 1 relates to a non-aqueous electrolyte secondary battery using a composite oxide containing lithium and manganese as the positive electrode active material. Manganese dissolves from lithium manganese oxide, the positive electrode active material, and due to various factors such as changes in the positive electrode active material, the deposition of dissolved manganese on the negative electrode surface and separator, and electrolyte degradation, the battery's cycle characteristics deteriorate and its remaining capacity decreases. Patent Document 1 discloses that, in order to reduce the dissolution of manganese, the battery contains oxides or carbonates such as la.
[0006] Patent Document 2 relates to a positive electrode active material for non-aqueous electrolyte secondary batteries, with the aim of improving discharge performance at low temperatures. Specifically, it proposes a positive electrode active material in which a compound containing rare earth elements and silicic acid and / or boric acid is in surface contact with a lithium transition metal complex oxide. This document discloses that the compound in contact with this surface can reduce the activation energy related to lithium-ion acceptance between the lithium transition metal complex oxide and the electrolyte, and improve ion conductivity, thereby enhancing discharge performance at low temperatures.
[0007] Patent document 3 relates to cathode materials for lithium-ion batteries, their manufacturing methods, and lithium-ion batteries, with the aim of improving cycle performance. To this end, it proposes adding additives to a Li raw material and a precursor containing Ni, Co, and Mn as starting materials in the manufacturing method of the cathode material, and then sintering it at a temperature above 700°C. This document discloses that this increases the aspect ratio of the cathode material grains, facilitating the insertion and extraction of lithium ions, thereby improving cycle performance.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2000-311689
[0011] Patent Document 2: Japanese Patent No. 6233406
[0012] Patent Document 3: Japanese Patent Publication No. 2023-515899 Summary of the Invention
[0013] Despite the various research and development efforts already undertaken for lithium-ion secondary batteries, there is still a need to further improve their performance.
[0014] The objective of this invention is to provide a novel additive for cathode materials capable of improving the performance of lithium-ion secondary batteries, a lithium-ion secondary battery cathode material comprising the additive, and a lithium-ion secondary battery. Here, "improved performance" refers to an increase in the performance of the lithium-ion secondary battery when the additive is added, compared to the case without the additive.
[0015] Specific performance improvements include increased discharge capacity during high-current discharge, or suppression of the increase in internal resistance (impedance) after cyclic testing.
[0016] To address the aforementioned issues, the inventors conducted in-depth research and discovered that by using compounds containing rare earth elements, boron, oxygen, and hydrogen as additives for positive electrode materials in lithium-ion secondary batteries, the performance of lithium-ion secondary batteries can be improved.
[0017] This invention is based on these findings, and its inventive summary is as follows.
[0018] (1) An additive for positive electrode material of non-aqueous electrolyte lithium-ion secondary battery, characterized in that it is a compound containing rare earth elements, boron, oxygen and hydrogen, and the compound is amorphous.
[0019] (2) The additive for the positive electrode material of lithium-ion secondary battery according to (1) is characterized in that the molar ratio of the rare earth element to the boron is 85:15 to 10:90.
[0020] (3) The additive for lithium-ion secondary battery cathode material according to (1) or (2) is characterized in that when heated from 30°C to 1000°C at a heating rate of 4°C / min, the mass reduction rate obtained by TG-DTA is more than 3% and less than 35%.
[0021] (4) An additive for lithium-ion secondary battery cathode material according to any one of (1) to (3), characterized in that the rare earth element is one or more selected from yttrium, lanthanum, cerium, praseodymium and neodymium.
[0022] (5) A lithium-ion secondary battery cathode material, characterized in that it comprises any one of the above (1) to (4) additives for lithium-ion secondary battery cathode materials and cathode active materials.
[0023] (6) The lithium-ion secondary battery cathode material according to (5) is characterized in that the cathode active material contains at least one of nickel, cobalt and manganese.
[0024] (7) A lithium-ion secondary battery, characterized in that it comprises the lithium-ion secondary battery positive electrode material described in (5) above.
[0025] (8) A lithium-ion secondary battery, characterized in that it comprises the lithium-ion secondary battery positive electrode material described in (6) above.
[0026] Invention Effects
[0027] In lithium-ion secondary batteries, the performance of lithium-ion secondary batteries can be improved when the cathode material additive of the present invention is added to the cathode material, compared with the case where no cathode material is added.
[0028] As a specific performance improvement, the capacity increases when the discharge voltage reaches 3.5V during high-current discharge. Since the discharge voltage range where voltage drop has a significant impact, the effect is compared using the discharge capacity at 3.5V.
[0029] Alternatively, it can suppress the rise in internal resistance (impedance) after cyclic testing. Attached Figure Description
[0030] Figure 1 The peak positions of the lanthanum-boron complex obtained by X-ray diffraction (XRD, CuKα source) are shown. (Example 1)
[0031] Figure 2The peak positions of the hydroxyl groups in the lanthanum-boron complex, obtained by Fourier transform infrared spectrophotometry (FT-IR), are shown. (Example 1)
[0032] Figure 3 An example is shown comparing the internal resistance based on the size of the arc corresponding to the interface migration resistance of the positive electrode.
[0033] Detailed description
[0034] The embodiments of the present invention will now be described in detail. These embodiments are merely examples of how the present invention can be carried out and should not be construed as limiting the scope of the invention.
[0035] The additive for the positive electrode material of a lithium-ion secondary battery, as one embodiment of the present invention, is an additive for the positive electrode material of a non-aqueous electrolyte lithium-ion secondary battery, and is a compound containing rare earth elements, boron, oxygen, and hydrogen.
[0036] There are no particular limitations on the cathode material of lithium-ion secondary batteries, as long as it can reversibly insert and extract lithium ions. Typical cathode materials include LiNiO2 (lithium nickel oxide), LiCoO2 (lithium cobalt oxide), LiMn2O4 (lithium manganese oxide), and LiMn... 1-x Fe x PO4 (lithium manganese iron phosphate) and their composite materials, etc.
[0037] By adding the cathode material additive of this embodiment to the cathode material, it is possible to obtain effects such as inhibiting cathode material degradation, improving ion conductivity at the interface between the cathode material and the electrolyte, and extending the lifespan of the lithium-ion secondary battery, thereby improving the performance of the lithium-ion secondary battery.
[0038] The cathode material additive in this embodiment contains rare earth elements. As the electrolyte for lithium-ion secondary batteries, a mixture is sometimes used containing fluorine compounds such as LiPF6 or LiBF4 as lithium salts, in ethylene carbonate and diethyl carbonate, which are non-aqueous solvents. These fluorine compounds sometimes react with moisture introduced from raw materials or during battery manufacturing, generating hydrofluoric acid. This acid can cause degradation of the cathode material. The rare earth elements contained in this embodiment are highly alkaline and therefore have high reactivity with acidic substances. Therefore, the rare earth elements react with the hydrofluoric acid that may be generated in the electrolyte, thereby inhibiting the degradation of the cathode material.
[0039] The positive electrode material additive in this embodiment contains boron. Boron lowers the activation energy related to lithium-ion acceptance between the positive electrode material and the electrolyte, and improves ion conductivity, thereby enhancing the performance of the lithium-ion secondary battery.
[0040] The cathode material additive in this embodiment contains oxygen. When the aforementioned rare earth elements and boron are added to the cathode material, compared to when they exist alone, it exhibits higher stability as a compound containing both rare earth elements and oxygen, i.e., a so-called composite oxide. In lithium-ion secondary batteries, it remains stable even under repeated charge-discharge cycles, resulting in extended battery life. In particular, because it is a composite compound containing rare earth elements and boron, the benefits of both are achieved.
[0041] The additive for the cathode material in this embodiment contains hydrogen. Regarding oxygen-containing compounds, boron-oxygen compounds, namely boron oxide (B₂O₃), typically have high hygroscopicity. High hygroscopicity allows moisture to enter the lithium-ion secondary battery, potentially accelerating its degradation. Furthermore, boron oxide itself has poor pulverizability and is difficult to micronize. The additive for the cathode material in this embodiment is a hydrogen-containing compound. That is, this compound is not a simple oxide but a hydrogen-containing complex compound, and may also be in the form of a hydroxide. Therefore, the hygroscopicity of this compound can be suppressed, and effects such as extending the lifespan of the lithium-ion secondary battery can be achieved. Furthermore, the burden of moisture management can be reduced during the manufacturing process of the lithium-ion secondary battery.
[0042] The presence of hydrogen in this compound was confirmed by the following method. In the case of hydrogen-containing compounds, compared to compounds containing hydroxyl groups, Fourier transform infrared spectroscopy (FT-IR) showed a difference in concentration between 3750 and 2500 cm⁻¹. -1 Peaks were confirmed within the range of 3750–2500 cm⁻¹. In the compounds of this embodiment, the inventors also confirmed peaks within the range of 3750–2500 cm⁻¹. -1 There are peaks within the range.
[0043] The above FT-IR measurements were performed using an IRTracer-100 Fourier transform infrared spectrophotometer manufactured by Shimadzu Corporation, within the wavenumber range of 7800–350 cm⁻¹. -1 The measurements were taken inside.
[0044] The compound containing rare earth elements, boron, oxygen, and hydrogen, which is used as an additive for the cathode material in this embodiment, is amorphous.
[0045] Amorphous materials lack a crystalline structure, with atoms arranged in an irregular, dense manner, resulting in fewer defects such as grain boundaries that hinder ion migration. Therefore, compared to crystalline materials, amorphous materials promote lithium-ion diffusion more effectively, making them the preferred additives.
[0046] The amorphous nature of the material was confirmed by the following method. When X-ray diffraction (XRD, CuKα source) was performed on the amorphous material, compared to crystalline materials, the following XRD pattern was obtained: diffuse broad peaks, the disappearance of peaks attributable to crystalline materials, and increased background. The same XRD pattern was also confirmed in the compound of this embodiment.
[0047] The above X-ray diffraction measurements were performed using a MiniFlex600 X-ray diffraction apparatus manufactured by Rigaku Corporation, with a step width of 0.01 deg, a scanning speed of 2.0 deg / min, and a measurement speed angle.
[0048] According to one embodiment of the present invention, in the compound used as an additive for the cathode material, the molar ratio of rare earth elements to boron is preferably 85:15 to 10:90, more preferably 70:30 to 20:80, and even more preferably 50:50 to 30:70. A higher molar ratio of rare earth elements facilitates reaction with acidic substances such as hydrofluoric acid, thereby enhancing the effect of inhibiting the degradation of the cathode material. Furthermore, a higher molar ratio of boron facilitates the reduction of the activation energy related to lithium-ion acceptance between the cathode material and the electrolyte, and improves ion conductivity, thus enhancing the performance of the lithium-ion secondary battery. However, if the molar ratio of either rare earth elements or boron is too high, only lanthanum oxide or boric acid will be deposited, which is not preferred. Therefore, a composite compound with a molar ratio of rare earth elements to boron of 85:15 to 10:90 is preferred. This allows for the simultaneous acquisition of the effects of both.
[0049] According to one embodiment of the present invention, when the positive electrode material is heated from 30°C to 1000°C at a heating rate of 4°C / min using additives, the mass reduction rate measured by TG-DTA is 3% or more and 35% or less. The lower the mass reduction rate measured by TG-DTA, the higher the stability, and the longer the lifespan of the lithium-ion secondary battery can be achieved. Typically, it is easier to suppress the increase in the internal resistance (impedance) of the battery after cycle testing. Preferably, the mass reduction rate can be 32% or less, 30% or less, 25% or less, 20% or less, 17.5% or less, 15% or less, or 12% or less.
[0050] According to one embodiment of the present invention, the rare earth element contained in the compound used as an additive for cathode material may be one or more selected from yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), and neodymium (Nd).
[0051] Rare earth elements are a collective term for 17 elements: scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). Rare earth elements are generally known to have similar properties; therefore, in embodiments of this invention, there is no particular limitation on the rare earth elements. On the other hand, because the global supply of rare earth elements is relatively small and their scarcity value is high, considering availability and cost, one or more elements selected from yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), and neodymium (Nd) may be used.
[0052] Next, a method for manufacturing an additive for the positive electrode of a lithium-ion secondary battery, which is one embodiment of the present invention, will be described.
[0053] For additives used in the positive electrode of lithium-ion secondary batteries, any method can be used as long as the compound that meets the requirements of this invention can be prepared. For example, examples include solid-phase reaction method, chemical vapor deposition method, hydrothermal method, wet synthesis method such as co-precipitation method, sol-gel method, spray pyrolysis method, etc.
[0054] The following are examples of synthesis using a wet synthesis method.
[0055] First, the raw materials containing the compounds in the additive are dissolved in water to prepare an aqueous solution. Examples of such raw materials include water-soluble salts such as nitrates, oxides, chlorides, sulfates, and acetates. As specific examples, boric acid can be used as the raw material for boron, and nitrates of La, Pr, Sm, Nd, Gd, Yb, Ho, Ce, and Y can be used as raw materials for rare earth elements. By dissolving these raw materials in water (preferably pure water or ion-exchanged water) at a specified molar ratio, an aqueous solution containing all the raw materials can be obtained. There are no particular limitations on the methods of dissolution and stirring.
[0056] Next, a precipitant is added to the raw material aqueous solution to co-precipitate the compound raw materials, thereby obtaining a precipitate (slurry). Regarding the precipitant, for example, precipitation can be achieved by controlling the pH to a pH range suitable for the precipitation of rare earth element cations, or by adding alkaline compounds such as ammonia or hydroxides (NaOH, KOH, etc.) to increase the pH (making it alkaline), thereby causing precipitation. Preferably, the precipitated slurry is heated to 70–90°C. There are no particular limitations on the heating method. Heating the slurry promotes hydroxyl bridging reactions (olation reactions) and oxygen bridging reactions in the precipitate. For example, the resulting slurry is heated to the range of 70–90°C and maintained for 4–10 hours (maturation). During this maturation, it is preferable to simultaneously perform industrially common stirring operations such as stirring with a stirring blade or circulation with a pump.
[0057] Alternatively, the raw material aqueous solution can be heated before adding the precipitant. Heating the raw material aqueous solution alters the nucleation behavior, thereby changing the aggregate structure of the precipitate.
[0058] The matured slurry undergoes solid-liquid separation and washing operations. There are no particular restrictions on the methods used for solid-liquid separation; industrial equipment such as centrifuges and filters can be used. The washing operation is used to reduce nitrogen and chloride ions in the hydroxide slurry containing boric acid and rare earth element cations, which are raw materials for the compound. For example, after dispersing the hydroxide in pure water, washing is performed using a centrifuge or filter. Preferably, this washing operation is continued until the content of nitrogen and chloride ions in the hydroxide is reduced to below 3% by mass.
[0059] The precipitate containing boric acid and rare earth element cations after washing is dried. The drying process uses industrial external heating or internal combustion drying equipment, for example, under conditions of hot air or heater temperature of approximately 40–200°C. Alternatively, spray drying can be performed. Through this drying process, a complex hydroxide containing boric acid and rare earth element cations, which are the raw materials for the compound, can be obtained.
[0060] For this composite hydroxide, heat treatment (also known as firing) can optionally be performed at a higher temperature. High-temperature heat treatment (firing) is preferred as it is expected to improve the stability and strength of the compound. The conditions for heat treatment (firing) can be adjusted appropriately. Typically, the lower limit of the heat treatment (firing) temperature is above the drying temperature; from the viewpoint of obtaining the aforementioned effects, higher temperatures are preferred, such as 250°C or above, or 300°C or above. The upper limit of the heat treatment (firing) temperature is not particularly limited as long as the amorphous nature of the composite hydroxide can be maintained; typically it can be below 500°C, or below 450°C, or below 400°C. Furthermore, the heat treatment (firing) time can be adjusted appropriately to obtain the desired properties; typically it can be 1 hour or more, preferably 3 hours or more. When heat treatment (firing) is performed for a long time, the resulting effect may tend to saturate, so it can also be set to within 5 hours. The atmosphere for heat treatment (firing) is not particularly limited; it can be in the atmosphere or an inert atmosphere. It should be noted that the heat treatment (firing) can be carried out in the state of the compound as a monomer, or in the state of the compound mixed with the positive electrode active material (as described below). In addition, the number of heat treatments (firings) is not limited to one; as long as the amorphous state can be maintained after heat treatment (firing), it can be repeated multiple times.
[0061] The resulting composite hydroxide can be pulverized as needed to adjust the particle size. Pulverization is only required to adjust the particle size to the desired level, and industrial pulverizing devices such as impact mills, roller mills, air jet mills, or ball mills can be used.
[0062] For the pulverized compound, the D50 (median particle size) of the secondary particles is determined by wet particle size distribution measurement. D50 is the particle size at which the cumulative frequency based on volume reaches 50%, also known as the median particle size.
[0063] The determination method was performed as follows: The sample was dispersed in ethanol solvent and ultrasonically dispersed for 5 minutes using a US-300AT ultrasonic homogenizer manufactured by Nippon Seiki Co., Ltd. Then, D50 was measured using an MT3300 manufactured by MicrotracBEL Co., Ltd., with the particle refractive index set to 2.17.
[0064] From the viewpoint of obtaining a good mixing state with the positive electrode active material, the particle size after pulverization is preferably D50=30μm or less, more preferably D50=10μm or less, and even more preferably D50=3μm or less.
[0065] According to one embodiment of the present invention, a positive electrode material for a lithium-ion secondary battery is provided. This positive electrode material contains the aforementioned additives for lithium-ion secondary battery positive electrode materials and a positive electrode active material. By adding the aforementioned additives for lithium-ion secondary battery positive electrode materials as described in one embodiment of the present invention to the positive electrode material, effects such as inhibiting the degradation of the positive electrode material, improving the ion conductivity at the interface between the positive electrode material and the electrolyte, and extending the lifespan of the lithium-ion secondary battery can be achieved, thereby improving the performance of the lithium-ion secondary battery.
[0066] There are no particular limitations on the method of adding additives to the positive electrode active material. The positive electrode material can be obtained by adding and mixing the additives. Industrial mixers such as V-type mixers, screw mixers, and air-flow mixers can be used for addition and mixing. Heat treatment is preferred after mixing, and more preferably at 200–500°C. The heat treatment after mixing can also serve as heat treatment (firing) for the additives. From the viewpoint of improving the adhesion between the additives and the positive electrode active material, heat treatment at 200°C or higher is preferred. Furthermore, from the viewpoint of maintaining the amorphous nature of the additives used in lithium-ion secondary battery positive electrode materials, heat treatment at 500°C or lower is preferred.
[0067] According to one embodiment of the present invention, the positive electrode active material may also contain at least one of nickel, cobalt, and manganese. The positive electrode active material can be appropriately selected from known positive electrode active materials commonly used in lithium-ion secondary batteries or all-solid-state batteries, depending on the desired battery capacity, voltage, and characteristics. As the positive electrode active material, materials capable of absorbing and releasing lithium ions are generally used. From this viewpoint, the positive electrode active material may contain at least one of nickel, cobalt, and manganese. Typical positive electrode active materials include lithium nickel oxide (LiNiO2), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), and lithium manganese iron phosphate (LiMn). 1- x Fe x PO4, or lithium nickelate Li(Ni-Co-Mn)O2 in which some nickel is replaced by cobalt and manganese.
[0068] Li(Ni-Co-Mn)O2 is a substance based on lithium nickelate, with a portion replaced by cobalt and manganese. It is known as a ternary or NCM-based cathode active material. It is preferred because it improves safety while reducing the amount of relatively expensive cobalt used. Typically, LiNi... 0.5 Co 0.2 Mn 0.3 O2 (NCM523).
[0069] According to one embodiment of the present invention, a lithium-ion secondary battery is provided. The positive electrode material comprises the aforementioned lithium-ion secondary battery positive electrode material. By including the aforementioned lithium-ion secondary battery positive electrode material as an embodiment of the present invention, the battery achieves effects such as suppressing positive electrode material degradation, improving ion conductivity at the interface between the positive electrode material and the electrolyte, and extending the lifespan of the lithium-ion secondary battery, thereby improving the performance of the lithium-ion secondary battery. Example
[0070] The present invention will now be described through examples and comparative examples. It should be noted that the present invention is not limited to these examples.
[0071] (Example 1)
[0072] Preparation of additives for positive electrodes
[0073] Ammonia was added to a mixed solution of lanthanum nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours in a round-bottom flask. During this time, adjustments were made to achieve a final La:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a Co-Jet System α-mkIV jet mill manufactured by SEISHINENTERPRISE Co., Ltd., to obtain an additive for lithium-ion secondary battery cathode materials with a particle size D50 of 1.8 μm. X-ray diffraction analysis was performed on the product obtained using this method, and the results are as follows: Figure 1 As shown, it was confirmed to be amorphous. Furthermore, after heating the product to 400°C in the atmosphere and performing X-ray diffraction again, no peaks originating from crystals were detected, indicating that it remains amorphous.
[0074] Preparation of positive electrode active material
[0075] Using a composite hydroxide with a Ni:Mn:Co molar ratio of 49:29:22, let the sum of the possible molar numbers of Ni, Co, and Mn contained in the composite hydroxide be denoted as M. T And mix with lithium carbonate, so that lithium relative to M T molar ratio (Li / M) T The molar ratio of the raw materials was 1.05. Next, the mixed powder was calcined in air at 870°C for 10 hours. Here, the molar ratio of the raw materials was adjusted to achieve a particle size of D50 = 5 μm after calcination and a composition of Li. 1.02 Ni 0.48 Mn 0.28 Co 0.22 O2.
[0076] Preparation of positive electrode composite materials
[0077] Next, the additive obtained above was added at an amount of 1.0% by mass (additive mass / total cathode composite material mass) and mixed with the cathode active material using a swing mixer manufactured by SEIWA GIKEN Co., Ltd., and then heat-treated in air at 400°C to obtain the cathode composite material.
[0078] Battery manufacturing
[0079] The aforementioned positive electrode composite material, acetylene black powder as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed in an N-methyl-2-pyrrolidone (NMP) solution at a mass ratio of 93:3.5:3.5 to prepare a positive electrode composite slurry. The positive electrode composite slurry was then coated onto aluminum foil and dried at 140°C. The punched positive electrode was then compressed at 28 MPa using a bench press. Afterward, it was vacuum dried at 120°C to form a positive electrode plate. A button cell was assembled using lithium metal foil as the negative electrode and 1 mol / L LiPF6 EC:DEC (volume ratio 3:7) as the electrolyte.
[0080] (Example 2)
[0081] Preparation of additives for positive electrodes
[0082] Ammonia was added to a mixed solution of lanthanum nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours in a round-bottom flask. At this point, adjustments were made to achieve a final La:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a Co-Jet System α-mkIV jet mill manufactured by SEISHINENTERPRISE Co., Ltd., to obtain an additive for lithium-ion secondary battery cathode materials with a particle size D50 of 1.8 μm. X-ray diffraction analysis was performed again after heating the product to 400°C in atmosphere; no peaks originating from crystals were detected, indicating that it is amorphous.
[0083] Preparation of positive electrode active material
[0084] Using a composite hydroxide with a Ni:Mn:Co molar ratio of 49:29:22, let the sum of the possible molar numbers of Ni, Co, and Mn contained in the composite hydroxide be denoted as M. T And it is precisely mixed with lithium carbonate, so that lithium relative to M T molar ratio (Li / M) TThe molar ratio of the raw materials was 1.05. Next, the mixed powder was calcined in air at 870°C. Here, the molar ratio of the raw materials was adjusted so that the composition after calcination was Li. 1.02 Ni 0.48 Mn 0.28 Co 0.22 O2.
[0085] Preparation of positive electrode composite materials
[0086] Next, the additive obtained above was added at an amount of 1.0% by mass (additive mass / total cathode composite material mass) and mixed with the cathode active material using a swing mixer manufactured by SEIWA GIKEN Co., Ltd., to obtain the cathode composite material. Subsequent processes were performed to prepare the battery in the same manner as in Example 1.
[0087] (Example 3)
[0088] Preparation of additives for positive electrodes
[0089] Ammonia was added to a mixed solution of lanthanum nitrate and boric acid to adjust the pH to 7.0. The solution was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final La:B molar ratio of 10:90. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was first pulverized using a mortar and pestle, and then further pulverized using a Co-Jet System α-mkIV jet mill manufactured by SEISHIN ENTERPRISE Co., Ltd., to obtain an additive for lithium-ion secondary battery cathode materials with a particle size D50 of 2.9 μm. The product was heated to 400°C in air and subjected to X-ray diffraction again; no peaks originating from crystals were detected, indicating it is amorphous. The following procedures were followed to prepare the battery in the same manner as in Example 1.
[0090] (Example 4)
[0091] Ammonia was added to a mixed solution of lanthanum nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final La:B molar ratio of 50:50. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a mortar and pestle and classified using a sieve with a sieve aperture of 45 μm to obtain an additive for lithium-ion secondary battery cathode materials with a particle size D50 = 18.3 μm. X-ray diffraction analysis was performed again on the product after heating it to 400°C in air; no peaks originating from crystals were detected, indicating it is amorphous. The following procedures were followed to prepare the battery in the same manner as in Example 1.
[0092] (Example 5)
[0093] Ammonia was added to a mixed solution of lanthanum nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final La:B molar ratio of 80:20. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a mortar and pestle and graded using a sieve with a 45 μm aperture to obtain an additive with a particle size D50 = 19.0 μm. The following procedures were followed to prepare the battery in the same manner as in Example 1. The product was heated to 400°C in atmospheric air and subjected to X-ray diffraction again. A small number of peaks originating from crystalline lanthanum nitrate were detected, but the overall product was amorphous. The following procedures were followed to prepare the battery in the same manner as in Example 1.
[0094] (Example 6)
[0095] Ammonia was added to a mixed solution of yttrium nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final Y:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a mortar and pestle and graded using a sieve with a 45 μm aperture to obtain an additive with a particle size D50 = 17.0 μm. The following procedures were followed to prepare the battery in the same manner as in Example 1. The product was heated to 400°C in air and subjected to X-ray diffraction again; no peaks originating from crystals were detected, indicating it was amorphous. The following procedures were followed to prepare the battery in the same manner as in Example 1.
[0096] (Example 7)
[0097] Ammonia was added to a mixed solution of cerium nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final Ce:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a mortar and pestle and graded using a sieve with a 45 μm aperture to obtain an additive with a particle size D50 = 16.6 μm. The following procedures were followed to prepare the battery in the same manner as in Example 1. The product was heated to 400°C in air and subjected to X-ray diffraction again; no peaks originating from crystals were detected, indicating it was amorphous. The following procedures were followed to prepare the battery in the same manner as in Example 1.
[0098] (Example 8)
[0099] Ammonia was added to a mixed solution of praseodymium nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final Pr:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a mortar and pestle and graded using a sieve with a 45 μm aperture to obtain an additive with a particle size D50 = 14.5 μm. The following procedures were followed to prepare the battery in the same manner as in Example 1. The product was heated to 400°C in air and subjected to X-ray diffraction again; no peaks originating from crystals were detected, indicating it was amorphous. The following procedures were followed to prepare the battery in the same manner as in Example 1.
[0100] (Example 9)
[0101] Ammonia was added to a mixed solution of neodymium nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final Nd:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a mortar and pestle and graded using a sieve with a 45 μm aperture to obtain an additive with a particle size D50 = 14.6 μm. The following procedures were followed to prepare the battery in the same manner as in Example 1. X-ray diffraction was performed again on the product after heating it to 400°C in the atmosphere. No peaks originating from crystalline material were detected, indicating that it was amorphous. X-ray diffraction was then performed again on the product after heating it to 400°C in the atmosphere. A small number of peaks originating from crystalline lanthanum nitrate were detected, but overall, it was amorphous. The following procedures were followed to prepare the battery in the same manner as in Example 1.
[0102] (Comparative Example 1)
[0103] Ammonia was added to a mixed solution of lanthanum nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours in a round-bottom flask. During this time, adjustments were made to achieve a final La:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a mortar and pestle, graded using a sieve with a sieve aperture of 45 μm, and then calcined in air at 800°C to obtain a crystalline compound composed of LaBO3 and LaB3O6 with a particle size of D50 = 8.1 μm. Subsequent procedures were performed to prepare the battery in the same manner as in Example 2. Furthermore, X-ray diffraction analysis was performed on the product obtained in Comparative Example 1, and the results are as follows: Figure 1 As shown, peaks of LaBO3 and LaB3O6 are present, thus confirming that it is crystalline.
[0104] (Comparative Example 2)
[0105] The battery was prepared in the same manner as in Example 1, except that lanthanum oxide (manufactured by Jiangxi Jinshiji Company, D50=3μm) was used as an additive for the positive electrode.
[0106] (Comparative Example 3)
[0107] Boric acid (manufactured by Fujifilm and Koichi Chemical Co., Ltd.) was pulverized using a fiber mixer MX-X701-T manufactured by Panasonic Corporation, and classified using a sieve with a mesh size of 45 μm. The resulting product was used as an additive for the positive electrode. Subsequent processes were performed to prepare the battery in the same manner as in Example 1.
[0108] (Comparative Example 4)
[0109] The battery was prepared in the same manner as in Example 2, except that lanthanum oxide (manufactured by Jiangxi Jinshiji Company, D50=3μm) was used as an additive for the positive electrode.
[0110] (Comparative Example 5)
[0111] Boric acid (manufactured by Fujifilm and Koichi Chemical Co., Ltd.) was pulverized using a fiber mixer MX-X701-T manufactured by Panasonic Corporation, and classified using a sieve with a sieve aperture size of 45 μm. The resulting product was used as an additive for the positive electrode. Subsequent processes were performed to prepare the battery in the same manner as in Example 2.
[0112] (Comparative Example 6)
[0113] The battery was prepared in the same manner as in Example 2, except that no additives were used for the positive electrode.
[0114] For the above-mentioned batteries, charge and discharge them under the following conditions.
[0115] Battery evaluation (initial activation, rate testing)
[0116] The button-type lithium secondary battery was evaluated using the ELF1024 charging and discharging device manufactured by Electrofield Co., Ltd.
[0117] The button-type lithium battery was placed in a 25℃ constant temperature bath, with the reference rate 1C set to 150mA / g, the upper limit voltage set to 4.2V, and the lower limit voltage set to 3.0V, for charge-discharge testing. The prepared button-type lithium secondary battery was first placed in a 25℃ constant temperature bath for 6 hours for initial activation.
[0118] During charging, a constant current and constant voltage charging process was performed at a rate of 30 mA / g (0.2C) and an upper limit of 4.2V, ending charging when the current dropped to 2 mA / g. During discharging, a rate of 30 mA / g (0.2C) was performed, with a lower discharge limit of 3.0V. This charging and discharging process was repeated three times under these conditions for initial activation. The resting time after charging and discharging was 30 minutes each.
[0119] Next, constant current and constant voltage charging was performed at a rate of 30 mA / g and an upper limit of 4.2 V, ending when the current dropped to 2 mA / g. For discharging, a rate of 75 mA / g (0.5C) was used, with a lower discharge limit of 3.0 V, and two charging and discharging cycles were performed. The resting time after charging and discharging was 30 minutes each.
[0120] Subsequently, constant current and constant voltage charging was performed at a rate of 30 mA / g and an upper limit of 4.2 V, ending when the current dropped to 2 mA / g. During discharging, the rate was 150 mA / g (1C), with the lower limit of discharge voltage set at 3.0 V, and two charging and discharging cycles were performed. The resting time after charging and discharging was 30 minutes each.
[0121] Next, constant current and constant voltage charging was performed at a rate of 30mA / g and an upper limit of 4.2V, and charging was stopped when the current dropped to 2mA / g. During discharging, the rate was 300mA / g (2C), and the lower limit of discharge voltage was set to 3.0V. Two charging and discharging cycles were performed. The resting time after charging and discharging was 30 minutes each.
[0122] Subsequently, constant current and constant voltage charging was performed at a rate of 30 mA / g and an upper limit of 4.2V, ending when the current dropped to 2 mA / g. During discharging, a rate of 750 mA / g (5C) was performed, with the lower limit of discharge voltage set at 3.0V, and two charging and discharging cycles were conducted. The resting time after charging and discharging was 30 minutes each.
[0123] Based on the results of the charge-discharge test, the discharge capacity (mAh / g) when the discharge voltage reaches 3.5V was calculated.
[0124] TG-DTA assay
[0125] For the positive electrode additives obtained in Examples 1 to 9 and Comparative Example 1, the mass reduction rate (%) obtained by TG-DTA was determined according to the following procedure.
[0126] A NETZSCH STA2500 Regulus thermogravimetric analyzer was used at 100 cm⁻¹. 3Nitrogen gas was introduced at a flow rate of 4 °C / min, and the temperature was measured in the range of 30–1000 °C under an inert atmosphere with a heating rate of 4 °C / min. The mass at 30 °C was designated as M1 (g), and the mass at 1000 °C was designated as M2 (g). The mass reduction rate (%) was calculated using the following formula.
[0127] Mass reduction rate (%) = [(M1-M2) / M1] × 100
[0128] As shown in Table 1, compared with the positive electrodes using additives from Comparative Examples 1-6, the positive electrodes using rare earth element-boron composite compounds from Examples 1-9 as additives showed no significant difference in charge-discharge tests of button-type lithium secondary batteries at 0.2C-1C, but the discharge capacity at 2C-5C, reaching a discharge voltage of 3.5V, increased. Specifically, it was 125 mAh / g or more at 2C and 71 mAh / g or more at 5C. This confirms that the rate performance of lithium-ion secondary batteries is improved by using the additive as an embodiment of the present invention. Furthermore, among the positive electrode additives from Examples 1-9, the maximum mass reduction rate (%) measured by TG-DTA was 31.4%. This confirms that the additive as an embodiment of the present invention exhibits certain stability even when heated to 1000°C.
[0129] [Table 1]
[0130]
[0131] (Example 10)
[0132] Preparation of additives for positive electrodes
[0133] Ammonia was added to a mixed solution of lanthanum nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours in a round-bottom flask. During this time, adjustments were made to achieve a final La:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a Panasonic MX-X701-T fiber mixer, classified using a 1mm sieve, and further heat-treated (fired) at 400°C in atmospheric air. The fired material was pulverized using a SEISHIN ENTERPRISE Co-JetSystem α-mkIV jet mill to obtain an additive for lithium-ion secondary battery cathode materials with a particle size D50 of 2.3 μm. X-ray diffraction analysis confirmed that the product obtained by this method was amorphous.
[0134] Preparation of positive electrode active material
[0135] Using a composite hydroxide with a Ni:Mn:Co molar ratio of 49:29:22, let the sum of the possible molar numbers of Ni, Co, and Mn contained in the composite hydroxide be denoted as M. T And mix with lithium carbonate, so that lithium relative to M T molar ratio (Li / M) T The molar ratio of the raw materials was 1.05. Next, the mixed powder was calcined in air at 870°C for 10 hours. Here, the molar ratio of the raw materials was adjusted to achieve a particle size of D50 = 5 μm after calcination and a composition of Li. 1.02 Ni 0.48 Mn 0.28 Co 0.21 O2.
[0136] Preparation of positive electrode composite materials
[0137] Next, the additive obtained above was mixed with the positive electrode active material using a swing mixer manufactured by SEIWA GIKEN Co., Ltd., with the amount of additive added being 1.0% by mass (additive mass / total positive electrode composite material mass), and then heat-treated in air at 400°C to obtain the positive electrode composite material.
[0138] Battery manufacturing
[0139] The aforementioned positive electrode composite material, acetylene black powder as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to an N-methyl-2-pyrrolidone (NMP) solution at a mass ratio of 93:3.5:3.5 to prepare a positive electrode composite slurry. The positive electrode composite slurry was then coated onto aluminum foil and dried at 140°C. The punched positive electrode was then compressed using a bench press. Afterward, it was vacuum dried at 120°C to form a positive electrode plate. A button cell was assembled using lithium metal foil as the negative electrode and 1 mol / L LiPF6 EC:DEC (volume ratio 3:7) as the electrolyte.
[0140] (Example 11)
[0141] Preparation of additives for positive electrodes
[0142] Ammonia was added to a mixed solution of lanthanum nitrate aqueous solution and boric acid aqueous solution to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final La:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a Panasonic MX-X701-T fiber mixer and graded using a 1mm sieve. The dried material was then pulverized again using a SEISHIN ENTERPRISE Co-Jet System α-mkIV jet mill to obtain an additive for lithium-ion secondary battery cathode materials with a particle size D50 = 1.5 μm. X-ray diffraction analysis of the product obtained using this manufacturing method confirmed that it was amorphous. The following steps were performed to prepare the battery in the same manner as in Example 10.
[0143] (Example 12)
[0144] The battery was prepared in the same manner as in Example 10, except that the positive electrode composite material was obtained without heat treatment at 400°C in air.
[0145] (Comparative Example 7)
[0146] Ammonia was added to a mixed solution of lanthanum nitrate and boric acid to adjust the pH to 7.0. The mixture was heated and stirred at 80°C for 6 hours using a round-bottom flask. During this time, adjustments were made to achieve a final La:B molar ratio of 30:70. The precipitate was then removed from the heated slurry, washed with water, and dried at 60°C. The dried material was pulverized using a Panasonic MX-X701-T fiber mixer, graded using a 1mm sieve, and then calcined in air at 800°C. The calcined material was then pulverized using a SEISHIN ENTERPRISE Co-Jet System α-mkIV mill to obtain a compound composed of LaBO3 and LaB3O6 with a particle size of D50 = 2.6 μm. Subsequent steps were performed to prepare the battery, similar to those in Example 10. It should be noted that X-ray diffraction analysis of the product obtained in Comparative Example 7 showed the presence of peaks in LaBO3 and LaB3O6, thus confirming that it is crystalline.
[0147] (Comparative Example 8)
[0148] The battery was prepared in the same manner as in Comparative Example 7, except that the positive electrode composite material was obtained without heat treatment at 400°C in air.
[0149] (Comparative Example 9)
[0150] The battery was prepared in the same manner as in Example 10, except that no positive electrode additive was used.
[0151] For the above-mentioned batteries, charge and discharge them under the following conditions.
[0152] Cyclic test
[0153] Cycling tests were conducted after initial activation and rate testing. Button-type lithium-ion batteries were placed in a 45°C constant-temperature bath and allowed to stand for 6 hours. During charging, constant current and constant voltage charging was performed at a rate of 75 mA / g (0.5C) with an upper limit of 4.25 V, and charging was stopped when the current dropped to 2 mA / g. During discharging, discharging was performed at a rate of 75 mA / g (0.5C) with a lower discharge limit of 3.0 V. The resting time after charging and discharging was set to 0 minutes. Under these conditions, 100 charge-discharge cycles were repeated.
[0154] Impedance measurement
[0155] For batteries that have undergone 100 charge-discharge cycles, they are charged in a 25°C constant temperature bath at a rate of 75mA / g (0.5C) to charge half of the capacity at the 100th cycle, so that the State of Charge (SOC) reaches 50%.
[0156] Subsequently, the internal resistance (impedance) was measured using a Bio-Logic VSP electrochemical measurement system in a 25°C constant temperature bath. The starting frequency was set to 200 kHz, the ending frequency to 10 mHz, and the sine wave amplitude to 10.0 mV. Measurements were repeated twice at each frequency, and the average value was taken. Figure 3 As shown, the internal resistance is compared based on the size of the arc corresponding to the interface migration resistance of the positive electrode.
[0157] TG-DTA assay
[0158] For the positive electrode additives obtained in Examples 10-12 and Comparative Examples 7-8, the mass reduction rate (%) obtained by TG-DTA was measured according to the above-described procedure.
[0159] As shown in Table 2, compared with the positive electrode using the additives of Comparative Examples 7-9, the positive electrode using the lanthanum-boron composite compound of Examples 10-12 as the additive exhibited lower internal resistance (impedance) after multiple charge-discharge tests of the button-type lithium secondary battery. This confirms that the additive used in one embodiment of the present invention can suppress the increase in internal resistance (impedance) of the lithium-ion secondary battery after multiple charge-discharge cycles, thereby contributing to a longer lifespan for the lithium-ion secondary battery.
[0160] [Table 2]
[0161]
Claims
1. An additive for use in positive electrode materials of non-aqueous electrolyte lithium-ion secondary batteries, characterized in that, It is a compound containing rare earth elements, boron, oxygen, and hydrogen, and the compound is amorphous.
2. The additive for lithium-ion secondary battery cathode material according to claim 1, characterized in that, The molar ratio of the rare earth element to the boron is 85:15 to 10:
90.
3. The additive for lithium-ion secondary battery cathode material according to claim 1, characterized in that, When the temperature is increased from 30℃ to 1000℃ at a heating rate of 4℃ / min, the mass reduction rate (%) determined by TG-DTA is greater than 3% and less than 35%.
4. The additive for lithium-ion secondary battery cathode material according to claim 1, characterized in that, The rare earth element is selected from one or more of yttrium, lanthanum, cerium, praseodymium, and neodymium.
5. A positive electrode material for a lithium-ion secondary battery, characterized in that, The additives for the positive electrode material of lithium-ion secondary batteries as described in any one of claims 1 to 4, as well as the positive electrode active material, are included.
6. The lithium-ion secondary battery cathode material according to claim 5, characterized in that, The positive electrode active material contains at least one of nickel, cobalt, and manganese.
7. A lithium-ion secondary battery, characterized in that, It includes the lithium-ion secondary battery cathode material as described in claim 5.
8. A lithium-ion secondary battery, characterized in that, It includes the lithium-ion secondary battery cathode material as described in claim 6.
Citation Information
Patent Citations
JP1987033406B2
Nonaqueous electrolyte secondary battery
JP2000311689A
Positive electrode material for lithium ion batteries, manufacturing method thereof, and lithium ion battery
JP2023515899A
